Das Problem des subjektiven Werturteils; The problem of subjective value judgment: On the calculations of the cost of a Russian gas embargo - Michael Hüther (Wirtschaftsdienst, 2022)
In der politischen Debatte um die richtige Reaktion des Westens auf den russischen Angriffskrieg auf die Ukraine steht neben den bereits beschlossenen Sanktionen ein sofortiges Gasembargo als Mittel im Raum, um den wirtschaftspolitischen Druck auf Russland zu erhöhen. Hier ist insbesondere ökonomische Expertise nötig, um die Politik in dieser Entscheidung zu beraten und die möglichen Kosten und Risiken für Deutschland transparent zu machen. Dabei sind die unvermeidlich zu setzenden subjektiven Werturteile offenzulegen. Auch muss differenziert über die Grenzen makroökonomischer Modelle gesprochen werden. – – In the political debate about the right Western reaction to Russia's war of aggression in Ukraine, an immediate gas embargo is being discussed and demanded in addition to the sanctions that have already been decided. The aim is to increase the economic pressure on Russia in order to end the war more quickly. Economic expertise is also needed here in order to advise politicians by making the possible economic costs and risks for Germany transparent. Doing so will disclose the unavoidable subjective value judgements. The limits of macroeconomic models must be discussed in a differentiated manner, and microeconomic findings as well as institutional conditions must be adequately acknowledged.
Keywords: A13; O13; P18; 330; Kriegsfolgen; Erdgaspolitik; Ausfuhrverbot; Makroökonomisches Modell; Deutschland; Russland